Evaluation of Baker’s Yeast (Saccharomyces cereviciae) In Enhancing Non Specific Immune Response and Growth of Nile Tilapia - Manurung, Usy N; Manoppo, Henky; Tumbol, Reiny A (e-Journal BUDIDAYA PERAIRAN, 2013)
This research was conducted to evaluate the efficacy of baker’s yeast in enhancing nonspecific immune response and growth of Nile tilapia. After two weeks of acclimatization in fiber tank, juveniles were put into glass aquarium at the density of 15 fish/ aquarium. Fish were fed pellet supplemented with baker’s yeast as treatment for four weeks at 5% of body weight per day, twice daily (08.00 and 17.00). Five doses of treatment used in this research were A (0 g yeast/kg pellet), B (10 g yeast/kg pellet), C (20 g yeast/kg pellet), D (30 g yeast/kg pellet), E (40 g yeast/kg pellet), Immune parameters included total leucocyte count (TLC) and phagocytosis activity were measured at the end of experiment. Fish growth was weighing at the end of research period. Anova was used to evaluate the effect of baker’s yeast on immune parameters and growth while to evaluate the different effect between treatment, Duncan test was used. Research result showed that after four week of feeding, TLC of fish fed diet supplemented with baker’s yeast significantly different compared to control fish. The highest TLC of fish was achieved in treatment B followed by treatment C. It was also found that phagocytosis activity of fish increased significantly in fish fed treatment diet with the highest PA was observed in treatment C. PA of fish in treatment C was different significantly compared to a treatment A, D and E but between treatment C and B, no significant difference was observed. Application of baker’s yeast in diet also significantly increased growth of fish (p=0,00). Fish fed diet supplemented with 20 g baker’s yeast/kg pellet has the highest weight gain compared to other fish in other treatments. It was concluded that the used of baker’s yeast at 20-30 g/kg pellet for four weeks could enhance nonspecific immune response and growth of Nile tilapia. Keywords: Saccharomyces cereviciae, total leucocyte count (TLC), Phagocytosis Activity, growth, Oreochromis niloticus